2002
DOI: 10.1029/2001gl014193
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the elevated land plume over the Arabian Sea and the Northern Indian Ocean during northeasterly monsoons and during the Indian Ocean experiment (INDOEX)

Abstract: We describe the dynamics of the formation of an elevated land plume over the Arabian Sea and northern Indian Ocean observed during the 1999 Indian Ocean Experiment (INDOEX). The presence of the elevated plume above the marine boundary layer for a depth of about 2000 m could be inferred from the thermodynamic profiles of the lower troposphere obtained from research vessels in 1997, 1998, and 1999, and in the lidar data obtained from aircraft during the INDOEX. Formation of the elevated plume was investigated fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
(14 reference statements)
3
14
0
Order By: Relevance
“…Relatively low O 3 values tend to correlate with clean oceanic air or air from lower‐emission continental regions. Previous studies have indicated that not all polluted areas produce ozone [ Raman et al , 2002; Reiner et al , 2001]. The lower portions of Figure 7 depict specific days, 8 and 13 March, where the color coding signifying vertical motion of the trajectories is generally subsident, consistent with patterns described by Raman et al [2002].…”
Section: Detailed Origins Of Tropospheric O3 Maximamentioning
confidence: 55%
See 1 more Smart Citation
“…Relatively low O 3 values tend to correlate with clean oceanic air or air from lower‐emission continental regions. Previous studies have indicated that not all polluted areas produce ozone [ Raman et al , 2002; Reiner et al , 2001]. The lower portions of Figure 7 depict specific days, 8 and 13 March, where the color coding signifying vertical motion of the trajectories is generally subsident, consistent with patterns described by Raman et al [2002].…”
Section: Detailed Origins Of Tropospheric O3 Maximamentioning
confidence: 55%
“…This analysis of the lower tropospheric ozone (Figures 1 and 4) emphasizes that pollution outflow tends to occur above the marine boundary layer, predominantly between 900 hPa (1 km) and 600 hPa (4 km), as explained for INDOEX in the works of Reiner et al [2001], Raman et al [2002], and Forêt et al [2005]. The lowest kilometer probably does not participate as pollutant outflow from a warm daytime continental mixed layer flows up and over a cooler marine layer.…”
Section: Detailed Origins Of Tropospheric O3 Maximamentioning
confidence: 80%
“…Along the Indian west coast, the altitude of the top of the pollution plume varied between 3-and 4-km msl, with the deeper plume depths being observed at 12:00 UTC (Chazette, 2003). Continental aerosols are generally observed to be mixed on the vertical throughout the depth of this land plume (Léon et al, 2001;Raman et al, 2002). Temperature profiles obtained from synoptic balloon soundings in Goa during the period running from 6 to 9 March 1999 show the presence of an elevated temperature inversion at this level, fluctuating between 3-and 4-km msl (not shown).…”
Section: Tracer Plume Diurnal Evolution and Propagation Over The Oceanmentioning
confidence: 99%
“…On some occasions, they exhibited high extinction‐to‐backscatter ratios implying the presence of absorbing aerosols, potentially arising from biomass burning regions over India [ Franke et al , 2003]. According to Raman et al [2002], the strength and coherence of the elevated plume was influenced by the diurnal variation of the structure of the upwind continental boundary layer.…”
Section: Introductionmentioning
confidence: 99%